INDUCTANCE CALCULATION CONSIDERING MAGNETIC SATURATION OF INTERIOR PERMANENT MAGNET SYNCHRONOUS MACHINES - Piotuch, Rafał (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2013)
In the paper a method for FEM calculation of self-inductances and d,q axis inductances determination is presented for Interior Permanent Magnet Synchronous Motors. FEM simulation results are compared with circuit model simulation results. In the research there is considered influence of magnetic saturation on circuit model parameters. It is a basis for further analysis of PM synchronous machine work.